Travelogues as the First Form of Travel Journalism - Niyozmetov Bunyodbek (European Science Publishing, 2023)
Of course, it is impossible for travel journalism to fully cover all the processes taking place in the world, new trends. But at the same time, considering the national characteristics without harming the national interests, determining the somewhat effective results that will be achieved in the process of striving towards the information society is a necessary production for our journalism today. Globalization and the rapid pace of current life, scientific and technical progress, new information technologies are rapidly changing our life and society in general. In such conditions, the demands of the human society for travel journalists are also changing. In the global news space, it is permissible for travel journalists to act as a politician, a statesman, a defender of the nation, and a bridge that establishes cultural ties between peoples.
Keywords: travel journalism, travelogue, myth, tourist, guide, social neetworks, travel blogs, journey